ASPEK HUKUM PELAKSANAAN PERJANJIAN KERJASAMA ANTARA BANK DENGAN LAYANAN JASA CASH MANAGEMENT (STUDI PADA PT. KELOLA JASA ARTHA CABANG MEDAN) - CHAIRUL ARIEF HARAHAP (PREMISE LAW JURNAL, 2016)
Cooperation agreement between PT Bank X (Persero) Tbk and PT. Kelola Jasa Artha devoted to operational ATM section aims to conduct replenishment or distribution of funds collected from the public can be used by the customer, in providing efficient service and quick to serve the customer the bank requires the other party to be able to provide the best and quick service for customers and also reduce the operational costs of distributing money to the cash machine to enhance the needs of modern society and the well-being of human life in general. The use of ATM in general does not always bring positive impact to the customer. In using ATM customer also often get problems that ultimately harm the customer. Customer complaints is a very valuable source of information for the evaluation of the improved performance of the company, whether its human resources as well as its products. Keywords: Agreements, Cooperation, Cash Management